Beginning Mac OS X programming - Trent, Michael, 1972- (Programmer to programmer., 2005)
Beginning Mac OS X ProgrammingEvery Mac OS X system comes with all the essentials required for programming: free development tools, resources, and utilities. However, finding the place to begin may be challenging, especially if you have no prior development knowledge. This comprehensive guide offers you an ideal starting point to writing programs on Mac OS X, with coverage of the latest release - 1.4 "Tiger."With its hands-on approach, the book examines a particular element and then presents step-by-step instructions that walk you through how to use that element when programming. You'll quickl